Belonging on Hold: Indonesian Temporary Migrants’ Everyday Politics in Australia - Farabi, Nadia; Salsabila, Ezraputi; Susiatiningsih, Rr. Hermini (Jurnal Hubungan Internasional, 2025)
This article examines the lived experiences of Indonesian temporary migrants in Australia by situating their mobility within a broader conceptual framework of temporary migration and stratified citizenship. While policy narratives often frame temporary migration as a “triple win” for sending states, receiving countries, and migrants themselves, this paper argues that such frameworks obscure the structural inequalities embedded within migration regimes. Drawing on critical literature and grounded in qualitative narratives, the article highlights how temporary migrants occupy an ambivalent space—economically needed yet politically excluded. It engages with theories of neoliberal migration governance and critiques the responsibilities of migrants who are expected to bear the burden of legal and social precarity. The analysis advances the concept of stratified citizenship to understand how migrants’ rights, access to services, and sense of belonging are fragmented and conditional. Focusing on Indonesian migrants’ everyday negotiations, the article calls for a reimagining of migration governance that centres political inclusion, dignity, and transnational state responsibility. In doing so, it contributes to ongoing debates in migration studies, citizenship theory, and international relations by foregrounding voices that are often silenced within dominant policy discourses. Keywords: Stratified Citizenship; Temporary Migration; Political Exclusion; Neoliberalism; Migrant Agency.